A Signal Segmentation‐Free Model for Electrocardiogram‐Based Obstructive Sleep Apnea Severity Classification. (18th January 2023) - Chen, Jeng-Wen; Lin, Shih-Tsang; Wang, Cheng-Yi; Lin, Chun-Cheng; Hsu, Kuan-Chun; Yeh, Cheng-Yu; Hwang, Shaw-Hwa
Abstract : Obstructive sleep apnea (OSA) has been a common sleep disorder for years, and polysomnography (PSG) remains the gold standard for diagnosing OSA. Nevertheless, PSG is a time and money consuming test, and patients have to wait long for arranging a PSG test in a hospital. In light of this, portable and wearable tools for OSA classification have been developed recently as a low‐cost and easy‐to‐use screening method before undergoing PSG. Using unsegmented electrocardiogram (ECG) signals, a deep neural network (DNN)‐based model is developed here to categorize OSA severity with the following features. First, the model takes unsegmented ECG signals recorded overnight as input, and then generates a four‐level scale as output. Since all the input ECG signals are unsegmented, the tremendous amount of effort spent on signal annotation can be fully saved. Second, the largest amount of data is used to test the model and consequently provide a high generalization ability, as compared with others in the literature. The overall outperformance of this work is highlighted at the end of this article, and this work is validated as an easy‐to‐use and effective screening tool for OSA accordingly. Abstract : Obstructive sleep apnea (OSA) is a common type of sleep disorder nowadays and significantly downgrades sleep quality and increases the risk of complications. This work develops a novel approach, using segmentation‐free, overnight electrocardiogram (ECG) signals and a deep learning model, to classify the four‐level OSA severity. This work is validated as an easy‐to‐use and effective screening tool for OSA.